Pathological bone changes in the mandibles of wild red deer (Cervus elaphus L.) exposed to high environmental levels of fluoride - Schultz, M; Kierdorf, U; Sedlacek, F; Kierdorf, H (Journal of anatomy, 1998)
A macroscopic, microscopic and scanning electron microscope study was performed on the pathological bone changes of the mandibles of wild red deer (n = 61) exhibiting severe dental fluorosis. The animals originated from a highly fluoride polluted area in Central Europe (Ore mountains and their southern foreland, Czech-German border region) and constituted 11.2 % of the studied red deer sample (n = 545) from this area. Pathologically increased wear and fracture of fluorosed teeth caused a variety of mandibular bone alterations, including periodontal breakdown, periostitis, osteitis and chronic osteomyelitis. As a further consequence of severe dental attrition, opening of the pulp chamber and formation of periapical abscesses were occasionally observed. In case of severe periodontal breakdown, loss of teeth from the mandibles was found. In addition to the inflammatory bone changes, the occurrence of osteofluorotic alterations was also diagnosed in the specimens with the highest bone fluoride concentrations (> 4000 mg F-/kg dry wt). These changes comprised extended apposition of periosteal bone onto the mandibular cortex as well as deformation of the mandibular body, which was attributed to a fluoride-induced osteomalacia. The present study provided circumstantial evidence that, in addition to fluoride induced dental lesions, the occurrence of marked periodontal disease and tooth loss is an important factor responsible for a reduction of life expectancy in severely fluorotic wild red deer.
Keywords: Microscopy, Electron, Scanning; Tooth Loss; mikroskopie elektronová rastrovací; Česká republika; vysoká zvěř; Německo; Fluorosis, Dental; Czech Republic; znečištění životního prostředí; Environmental Pollution; Mandible; zvířata; dentální fluoróza; Fluorides; Germany; Deer; ztráta zubů; mandibula; fluoridy; Animals